Language and the Relationship of Proxemics in Communication among the Malay Community I - Sujud, Arbaie; Abd Rahim, Normaliza; Ahmad, Zamri; Roslan, Siti Nur Aliaa; Hassan, Hamisah Zaharah (The International Journal of Interdisciplinary Social Sciences, 2008)
This research is related to proxemics which was carried out by Edward Hall in 1950s and 1960s. The objectives were to find out the use of space and how the differences in using the space influenced a person when he/she in the process of communication. The use of space and the distance of a person when he/she communicate will make an individual in a calm situation or vice versa. In the context of the Malay traditional house architecture and design in states in Malaysia namely; Perlis, Selangor, Trengganu and Melaka were found that the distance of the three or communication space were used, i.e., intimacy, personal and social or public. Besides that, it was found that space and distance made language and diction used for communication verbal or nonverbal. Obviously, the architecture and design of Malay traditional house showed the interaction pattern and communication in the Malay community.